Geochemical characteristics and genesis of sandstone-type uranium deposits, Sierra Pintada District, San Rafael, Mendoza, Argentina - Nicolli, Hugo B.; Gamba, Mirtha A.; Ferreyra, Raúl E. (Geoinstitut Belgrado (Checoslovaquia), 1981)
Fil: Nicolli, Hugo B. Comisión Nacional de Energía Atómica; Argentina